Dilute sulfuric acid fractionation of Korean food waste for ethanol and lactic acid production by yeast. (April 2018) - Kim, Yong Seon; Jang, Ji Yeon; Park, Seong Jik; Um, Byung Hwan
Graphical abstract: Highlights: Fermentation of Korean food waste can be applied to produce lactic acid and ethanol. The optimization was conducted the fractionation by response surface methodology. The fermentable sugars were enough to be used to produce biofuels and biochemicals. Abstract: Fermentation of food waste biomass can be used to produce biochemicals such as lactic acid and ethanol in a cost-effective manner. Korean food waste (KFW) dewatered by a screw press contains 23.1% glucan on a dry basis and is a potential raw material for the production of ethanol and lactic acid through fermentation. This study was conducted to optimize the dilute acid fractionation conditions for KFW fermentation with respect to the H2 SO4 concentration (0–0.8% w/v), temperature (130–190 °C), and residence time (1–128 min) using response surface methodology. Dilute sulfuric acid fractionation was carried out using a 30-mL stainless steel reactor under conditions, and then the dilute acid fractionation was scaled-up in 1-L and 7-L stainless steel reactors under the optimal conditions. The hydrolysate was concentrated, liquid-liquid extracted and neutralized for lactic acid and ethanol production. The highest concentration of glucose obtained from the KFW was 26.4 g/L using fractionation with 0.37% w/v H2 SO4 at 156 °C for 123.6 min. Using recombinant Saccharomyces cerevisiae containing a codon-optimized lactate dehydrogenase, the yield of lactic acid and ethanol was 77% of the theoretical yield for 17.4 g/L of fermentable sugar at pH 5.5. Additionally, the yield of ethanol produced by Issatchenkia orientalis was 89% of the theoretical yield for 25 g/L of fermentable sugar at pH 3.